DOMINASI KOMUNIKASI ISTRI DALAM KELUARGA PADA MASYARAKAT KECAMATAN RANAH BATAHAN TINJAUAN PERSPEKTIF ISLAM - Hayati, Riska; Rubino; Simamora, Irma Yusriani (Universitas Islam Negeri Raden Intan Lampung, 2025)
Communication in the family plays a very important role in maintaining harmonious relationships between family members. In this case, the dynamics of communication between husband and wife often reflect social changes that occur in society. One interesting phenomenon to study is the dominance of communication by the wife in the family, which is influenced by social, cultural, educational, and economic factors. This study focuses on the community of Ranah Batahan District, West Sumatra, using a qualitative approach and case study design. Data collection was carried out through interviews, observations, and documentation, which were then analyzed using an interactive model and a phenomenological approach. The conclusions of the study were drawn inductively. The results of the study showed that the dominance of wife communication was influenced by economic factors (the wife as the main breadwinner), education, and the husband's passive or less assertive character. From an Islamic perspective, the wife's dominance in family communication does not conflict with the sharia, as long as it maintains the principles of deliberation, mutual respect, and fair division of roles according to the couple's abilities. Islam emphasizes justice, not domination, in household relationships. This finding confirms that the wife's dominance in communication is acceptable in Islam, as long as it does not cause an imbalance in responsibility and maintains family harmony in accordance with the guidance of the Qur'an and Sunnah.